ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KINERJA PENYULUH PERTANIAN DALAM RANGKA MENINGKATKAN KINERJA PENYULUH PERTANIAN KABUPATEN SERDANG BEDAGAI - Risa Kartika Lubis (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2016)
Extension is an important activity in agriculture and extension process is spearheading the delivery of information and agricultural programs of government to be one determinant of the success of agriculture in Serdang Bedagai. Lack of agricultural extension workers of the task - the task of agricultural extension is not comparable with the managerial ability of extension workers such as extension workers who can not advance the farmer groups such as developing leadership skills, entrepreneurial and managerial capacity of farmers. Performance of agricultural extension in Serdang Bedagai decline is a phenomenon that should get the attention of the parties concerned.The aim of this study was to find the factors that affect the performance of the agricultural extension Bedagai Serdang. Find policy alternatives for improving the performance of agricultural extension Serdang BedagaiThis type of research is quantitative research. Questionnaires were distributed by purposive sampling to 103 extension agents who work in Serdang Bedagai.From the analysis, obtained that Based on the analysis of questionnaires distributed to 103 respondents, the value of the coefficient of determination (R Square) of 0.840, which means 84% of the performance of agricultural extension is affected by the variable reward system, the availability of facilities and infrastructure, commodities dominant target area, while 16 % influenced by other variables. A significant difference between the variable awards simultaneously, the availability of facilities and infrastructure, the dominant commodities target area with the performance of agricultural extension. Based on testing in partial award, the availability of facilities and infrastructure, the dominant commodities target area a significant difference to the performance of agricultural extension. Variable award has the most dominant influence on the performance of agricultural extension.